2019
DOI: 10.5606/archrheumatol.2019.6752
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Olfactory Bulb Volumes in Patients With Rheumatoid Arthritis: A Retrospective Study

Abstract: Objectives: This study aims to evaluate olfactory bulb (OB) volume in patients with rheumatoid arthritis (RA) using magnetic resonance imaging. Patients and methods: In this retrospective and case-control study, OB volumes of 37 RA patients (6 males, 31 females; mean age 48.6±10.8 years; range, 18 to 65 years) were compared with those of 36 healthy control subjects (5 males, 31 females; mean age 46.5±6.9 years; range, 22 to 62 years). OB images were gained with a protocol of 256×256 matrix and a 24-cm field of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Olfactory dysfunction is defined as a new clinical feature of RA and is considered an indicator of active disease and poor prognosis and is known to significantly negatively affect patients' quality of life. [1][2][3] Sayilir et al 15 also reported lower OB volumes in patients with RA than in the control group; these results are similar to those observed in our study. However, in our study, we additionally evaluated OS depth, as well as the association between olfactory measurements and disease duration, biological agent administration, and systemic inflammatory biomarkers (CRP, NLR, red blood cell distribution width, and the mean platelet volume).…”
Section: Discussionsupporting
confidence: 92%
“…Olfactory dysfunction is defined as a new clinical feature of RA and is considered an indicator of active disease and poor prognosis and is known to significantly negatively affect patients' quality of life. [1][2][3] Sayilir et al 15 also reported lower OB volumes in patients with RA than in the control group; these results are similar to those observed in our study. However, in our study, we additionally evaluated OS depth, as well as the association between olfactory measurements and disease duration, biological agent administration, and systemic inflammatory biomarkers (CRP, NLR, red blood cell distribution width, and the mean platelet volume).…”
Section: Discussionsupporting
confidence: 92%
“…IL-6 exposure enhances neurogenesis over the short term, but depletes the neural stem cell pool over the long term (40). However, a decrease in the OB volume was reported in RA (42). Therefore, it will be of interest to investigate whether the persistently elevated expression of IL-6 in the OB under arthritic conditions affects neurogenesis in the SVZ-RMS-OB, and this is a topic for future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 exposure enhances neurogenesis over the short term but depletes the neural stem cell pool over the long term [ 42 ]. However, decreased OB volume has been reported in patients with RA [ 44 ]. Therefore, it will be of interest to investigate whether the persistently elevated expression of IL-6 in the OB under arthritic conditions affects neurogenesis in the subventricular zone-rostral migratory stream-OB, which is a topic for future investigation.…”
Section: Discussionmentioning
confidence: 99%